Sequential Continuous Mixotrophic and Phototrophic Cultivation Might Be a Cost-Effective Strategy for Astaxanthin Production From the Microalga Haematococcus lacustris - Khazi, Mahammed Ilyas; Shi, Liangtao; Liaqat, Fakhra; Yang, Yuxin; Li, Xin; Yang, Duanpeng; Li, Jian (Frontiers in Bioengineering and Biotechnology, 2021)
Although Haematococcus lacustris has been developed for astaxanthin production for decades, the production cost is still high. In order to modify the production processes, we proposed a novel strategy of cultivation, featured by sequential indoor continuous mixotrophic cultivation for the production of green cells followed by outdoor phototrophic induction for astaxanthin accumulation. The continuous mixotrophic cultivation was first optimized indoor, and then the seed culture of mixotrophic cultivation was inoculated into outdoor open raceway ponds for photoinduction. The results showed that mixotrophically grown cultures could efficiently grow without losing their photosynthetic efficiency and yielded higher biomass concentration (0.655 g L−1) and astaxanthin content (2.2% DW), compared to phototrophically grown seed culture controls. This novel strategy might be a promising alternative to the current approaches to advance the production technology of astaxanthin from microalgae.